Anti-inflammatory and gut microbiota regulatory effects of walnut protein derived peptide LPF in vivo. (February 2022) - Zhi, Tongxin; Hong, Dan; Zhang, Zijie; Li, Siting; Xia, Junxia; Wang, Chong; Wu, Yongling; Jia, Yingmin; Ma, Aijin
Graphical abstract: Highlights: The walnut peptide LPF showed significant anti-inflammatory effects in vivo . The walnut peptide LPF can regulate the dysbiosis of gut microbiota induced by DSS. The study provides a theoretical basis for walnut peptides as food additives. Abstract: Walnut peptides have been reported to exhibit diverse activities. In this study, we investigated the protective and recovery effects of the walnut derived peptide leucine-proline-phenylalanine (LPF) on dextran sulfate sodium (DSS)-induced colitis in mice. The peptide LPF mitigated the severity of symptoms during the development phase of colitis, as evidenced by changes in body weight, disease activity index score, and serum inflammatory cytokine levels. Moreover, the treatment groups showed beneficial effects, including increased colon length, reduced colonic cell apoptosis, decreased production of inflammatory factors, and expansion of splenic regulatory T cells during the recovery period. Additionally, 16S rDNA sequencing results indicated that 100 mg/kg LPF (M group) reversed the dysbiosis of gut microbiota in colitis mice. This included partial recovery of diversity of microbiota, increase in relative abundance of the family Lachnospiraceae and Ruminococcaceae during the development phase of colitis. Additionally, the composition of gut microbiota in the M group was constantly improved during the recovery period of colitis, showing increased relative abundance of beneficial genera and decreased abundance of potentially harmful genera compared with that in the DSS group. In summary, the peptide LPF could contribute to remission of colitis symptoms and restoration through reduction in cell apoptosis, anti-inflammatory effects, and regulation of gut microbiota.